THE CHALLENGE OF BEING A UNIVERSITY PROFESSOR FACING THE EDUCATIONAL SCENARIO - Luiza Escorsin, Andrea; Da Silva Milhomem, Poliana; Soares Lima Silva, Vanessa; Carvalho Do Nascimento Silva, Cleres (Revista Gênero e Interdisciplinaridade, 2023)
This paper aims to analyze how Higher Education teachers perceive different agents in the educational field, and how tensions and difficulties are managed. The article is based on a bibliographic review on didactic formation and the role of the university teacher for society, and also on data from semi-structured interviews with online questionnaire of closed and open questions, which were analyzed quantitatively and qualitatively. Our results reveal difficulties related to classroom management and similarities between teachers with regard to: didactics, the value given to the support (or not) of the educational entity, and the number of activities performed and methods used.